FDG PET/CT for rectal carcinoma radiotherapy treatment planning: comparison of functional volume delineation algorithms and clinical challenges. (8th September 2014) - Withofs, Nadia; Bernard, Claire; van der Rest, Catherine; Martinive, Philippe; Hatt, Mathieu; Jodogne, Sebastien; Visvikis, Dimitris; Lee, John A.; Coucke, Philippe A.; Hustinx, Roland
Abstract : PET/CT imaging could improve delineation of rectal carcinoma gross tumor volume (GTV) and reduce interobserver variability. The objective of this work was to compare various functional volume delineation algorithms. We enrolled 31 consecutive patients with locally advanced rectal carcinoma. The FDG PET/CT and the high dose CT ( CT RT ) were performed in the radiation treatment position. For each patient, the anatomical GTV RT was delineated based on the CT RT and compared to six different functional/metabolic GTV PET derived from two automatic segmentation approaches (FLAB and a gradient‐based method); a relative threshold (45% of the SUV max ) and an absolute threshold ( SUV > 2.5 ), using two different commercially available software (Philips EBW4 and Segami OASIS). The spatial sizes and shapes of all volumes were compared using the conformity index (CI). All the delineated metabolic tumor volumes (MTVs) were significantly different. The MTVs were as follows ( mean ± SD ) : GTV RT ( 40.6 ± 31.28 ml ) ; FLAB ( 21.36 ± 16.34 ml ) ; the gradient‐based method ( 18.97 ± 16.83 ml ); OASIS 45 % ( 15.89 ± 12.68 ml ); Philips 45 % ( 14.52 ± 10.91 ml ) ; OASIS 2.5 ( 41.62 ± 33.26 ml ) ; Philips 2.5 ( 40 ± 31.27 ml ) . CI between these various volumes ranged from 0.40 to 0.90. The mean CI between the different MTVs and the GTV CT was < 0.4 . Finally, the DICOM transfer of MTVs led to additional volume variations. In conclusion, we observed large and statistically significant variations in tumor volume delineation according to the segmentation algorithms and the software products. The manipulation of PET/CT images and MTVs, such as the DICOM transfer to the Radiation Oncology Department, induced additional volume variations. PACS number: 87.55.D‐